Truth, law and literature - Wojtuń, Maciej (Acta Universitatis Lodziensis. Folia Iuridica, 2014)
The ethos of the lawyer in western societies is mainly founded on a culture of the Enlightenment. In effect, it tends to treat law in a purely rational and instrumental manner. The Law and Literature movement, as opposed to this traditional approach, searches for lost dimensions of the lawyer’s ethos, trying to discover interpretative, rhetoric and narrative aspects in the practice of law.